Behavior of high-strength stainless steel S600E welded I-section beams. (January 2023) - Zheng, Baofeng; Zhang, Sibo; Yu, Lei; Shu, Ganping; Dong, Shutong
Abstract: S600E is a new type of high-strength stainless steel with sorbite microstructure. Its yield strength is as high as 600 MPa, and its cost is lower than the commonly used stainless steel due to its low content of precious metallic elements Ni and Cr. This paper studied the bending capacity of high-strength stainless steel S600E welded I-section beams with lateral-torsional buckling. Tests on seven I-section beams were performed using an innovative four-point bending test rig. Thereafter, comparisons between the bending capacities and the values predicted using the current Eurocode, American code, and Chinese specification were conducted. The results showed that the predictions of the three existing codes were all conservative. Finite element models for the beams were established and verified, meanwhile, parametric analyses based on the simplified models were carried out on the influence of key parameters. Subsequently, through the results of the test and finite element analysis, the design formula for the lateral-torsional buckling was modified and the design formula for the local buckling in the companion study was verified. The complete design procedure of high-strength stainless steel S600E I-section beams was developed by the combination of the two formulae. Finally, to prove the accuracy of the design method proposed in this paper, comparisons between the predictions of the proposed method with the test data and four hundred finite element models were conducted.